Synthesis of a Molecule with Four Different Adjacent Pnictogens. Issue 35 (21st July 2016) - Hinz, Alexander; Schulz, Axel; Villinger, Alexander
Abstract: The synthesis of a molecule containing four adjacent different pnictogens was attempted by conversion of a Group 15 allyl analogue anion [Mes*NAsPMes*] − (Mes*=2, 4, 6‐tri‐ tert ‐butylphenyl) with antimony(III) chloride. A suitable precursor is Mes*N(H)AsPMes* (1 ) for which several syntheses were investigated. The anions afforded by deprotonation of Mes*N(H)AsPMes* were found to be labile and, therefore, salts could not be isolated. However, the in situ generated anions could be quenched with SbCl3, yielding Mes*N(SbCl2 )AsPMes* (4 ). Abstract : Connect four : The synthesis and characterization of Mes*N(SbCl2 )AsPMes*, a molecule containing four adjacent different pnictogens was achieved in the reaction of Li[Mes*‐NAsP‐Mes*] with SbCl3 (see scheme).